2019
DOI: 10.1016/j.rmcr.2019.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Sudden cardiac death due to primary malignant pericardial mesothelioma: Brief report and literature review

Abstract: Sudden cardiac death is an unexpected clinical condition that typically occurs due to a cardiac cause, generally within 1 h of symptom onset, in people with known or unknown cardiac disease. Primary malignant pericardial mesothelioma, as a cause of sudden death, is an uncommon consequence of a rare disease. Herein, we present a case of cardiac tamponade due to a primary pericardial mesothelioma. Cytological, histopathology and gross post-mortem findings, in a previously asymptomatic 46-old-year man, are report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
4
0
2
Order By: Relevance
“…La capacidad invasiva de estructuras adyacentes y de producir metástasis a distancia, también van a ser factores importantes para evaluar individualmente el pronóstico; aunque la muerte precoz suele estar definida por la restricción severa que causa, aun cuando la infiltración se limita al pericardio [2,5,9].…”
Section: Recomendacionesunclassified
See 1 more Smart Citation
“…La capacidad invasiva de estructuras adyacentes y de producir metástasis a distancia, también van a ser factores importantes para evaluar individualmente el pronóstico; aunque la muerte precoz suele estar definida por la restricción severa que causa, aun cuando la infiltración se limita al pericardio [2,5,9].…”
Section: Recomendacionesunclassified
“…EI mesotelioma es un tumor de origen mesodérmico, que suele aparecer en peritoneo o pleura y raramente lo hace en el pericardio, como mesotelioma pericárdico primario (MPP) [1], es aún el tumor primario maligno de pericardio más común [2]. Las primeras menciones del mesotelioma se remontan a los años 60, cuando se describe inicialmente como un diagnóstico de exclusión post-mortem, tras buscar de forma exhaustiva en la autopsia otro foco primario de malignidad [3].…”
Section: Introductionunclassified
“… 4 Accordingly, many patients are diagnosed at an advanced stage of the disease or post-mortem. 5 Thereby the overall survival of patients suffering from PPM is poor, with a median survival of 3 months without surgical intervention. 6 Therapeutic options for PPM include resecting surgery, radiation, and chemotherapy with only limited data on treatment efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Malignant disease of the pericardium, either primary or metastatic, is known to be the cause of pericardiac effusion. 1,2 The major etiological factors of malignant pericardial effusion include lung cancer, breast cancer, lymphoma, and leukemia, whereas cardiac metastasis from gynecological malignancies is known to be extremely rare. As far as the authors are aware, endometrial mixed carcinoma has never been reported to cause malignant pericardial effusion.…”
Section: Introductionmentioning
confidence: 99%